Hallux valgus surgery in children with cerebral palsy: A systematic review. Issue 4 (June 2022) - Lewis, T.L.; Patel, K.; Shepherd, K.L.; MacInnes, P.; Ray, R.; Kokkinakis, M.
Abstract: Background: Children with cerebral palsy are highly likely to develop foot deformities, some of which may require surgical intervention. Hallux valgus is a common forefoot deformity which can cause issues with pain, footwear, orthotic splints and soft tissues. It remains unclear what the optimal surgical treatment is for children with cerebral palsy and hallux valgus deformity. Objective: To systematically review studies reporting the clinical and radiological outcomes of surgical correction of hallux valgus deformity in children with cerebral palsy. Methods: A systematic review of studies published in electronic databases (Medline, Embase, Pubmed and Cochrane library) from inception until January 2021. Keywords related to hallux valgus and cerebral palsy were included. Results: 58 studies were identified of which 7 met the criteria for inclusion. 200 feet in 134 patients with a mean age of 13.5 years were included, with a mean follow up period of 43 months. A range of clinical and radiographic outcomes were assessed. A treatment framework for the assessment and management of hallux valgus in children with cerebral palsy based on the published evidence is presented. Conclusion: Non-ambulant children with cerebral palsy with symptomatic hallux valgus should primarily undergo first MTPJ arthrodesis whilst those who are ambulant should undergo first metatarsal osteotomy± soft tissue correction.